Cuckoo ray (Leucoraja naevus) in subareas 6 and 7, and in divisions 8.a–b and 8.d (West of Scotland, southern Celtic Seas, and western English Channel, Bay of Biscay) - ICES (Browse ICES content by Type, 2022)
Description not yet available.